2023
DOI: 10.1001/jamanetworkopen.2023.33944
|View full text |Cite
|
Sign up to set email alerts
|

Visit and Between-Visit Interaction Frequency Before and After COVID-19 Telehealth Implementation

Sarah Nouri,
Courtney R. Lyles,
Elizabeth B. Sherwin
et al.

Abstract: ImportanceTelehealth implementation associated with the COVID-19 public health emergency (PHE) affected patient–clinical team interactions in numerous ways. Yet, studies have narrowly examined billed patient-clinician visits rather than including visits with other team members (eg, pharmacists) or between-visit interactions.ObjectiveTo evaluate rates of change over time in visits (in-person, telehealth) and between-visit interactions (telephone calls, patient portal messages) overall and by key patient charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The need for social distancing and the uptake of telemedicine during the COVID-19 pandemic led to a rise in patient portal use, which could improve the reach of such strategies [ 88 ]. The uptake in patient portal during the pandemic was also associated with a rise in “e-visits,” which were communications between patients and clinicians between in-person visits [ 89 , 90 ]. This led to health care systems to bill for these messages following existing federal rules [ 90 , 91 ], which in turn may limit the use of patient portals and impact their effectiveness as an implementation strategy.…”
Section: What Are the Challenges?mentioning
confidence: 99%
“…The need for social distancing and the uptake of telemedicine during the COVID-19 pandemic led to a rise in patient portal use, which could improve the reach of such strategies [ 88 ]. The uptake in patient portal during the pandemic was also associated with a rise in “e-visits,” which were communications between patients and clinicians between in-person visits [ 89 , 90 ]. This led to health care systems to bill for these messages following existing federal rules [ 90 , 91 ], which in turn may limit the use of patient portals and impact their effectiveness as an implementation strategy.…”
Section: What Are the Challenges?mentioning
confidence: 99%
“…For example, a report from the US Department of Health and Human Services found that Hispanic individuals had substantially higher rates of telemedicine use than White individuals . Other studies have found the opposite, that Black and Hispanic individuals are less likely to use telemedicine than White individuals . Similarly, mixed results in telemedicine use have been found by income or other markers of socioeconomic status …”
Section: Introductionmentioning
confidence: 95%
“…However, Black and Hispanic individuals in those communities may be less likely to use telemedicine than their White neighbors. This may explain why several studies that used data from a single health system, in which patients typically come from within a limited geographic area, found lower rates of telemedicine use among Black and Hispanic individuals. The question of differences in telemedicine use by race and ethnicity and what underlies those differences is critical to guide policy interventions.…”
Section: Introductionmentioning
confidence: 99%